DEVELOPMENT OF INSTRUMENTS TESTING STUDENTS' MATHEMATICAL CRITICAL THINKING SKILLS ONE-VARIABLE LINEAR EQUATION MATERIAL - Oliah, Siti; Mulyanti, Yanti; Nurcahyono, Novi Andri (Prima: Jurnal Pendidikan Matematika, 2024)
Therefore, critical thinking skills need to be possessed by students. This is in line with what was stated variable linear equation (PLSV) material. The research method used in this study is development research with the ADDIE model. The subjects of this research were grade VIII G students at MTsN 3 Sukabumi with a total of 22 respondents. The object used is the instrument of critical thinking ability. The data collection technique in this study used feasibility tests from experts or validators as many as 3 experts and students as respondents. The results showed that the instruments developed were in the valid category with t_hitung>t_tabel, had a reliability index of 0.467 with the medium category, and the distinguishing power of each question item was in the index of 0.40<DP<0.70 with a good category and for the level of difficulty there were two instrument items in the range of 0.30<TK≤0.70 with the medium category and one question item in the difficult category with a value range of 0.00<TK≤0.30. Based on the feasibility test from experts and the results of the validity test of each question item, reliability, differentiating power and level of difficulty, the instrument is good and can be used.